Acerca de las representaciones de ‘thiasos’ marino en los mosaicos romanos tardo-antiguos de Hispania - Neira Jiménez, Luz (Antigüedad y Cristianismo, 1991)
This is a study of the theme of the marine thiasos of the Roman mosaics in the Hispanic environment during the late antiquity. There is a great variety in the repertory, and the rest of the Empire. The enormous dispersion of these themes vrhich in the beginning paved the thermal rooms later were used as flooring In other rooms of the houses, villas and including the tombs. For this reason if is not posible to sign them an exclusive termal carácter.